Adverse events associated with the use of radiopharmaceuticals: A prospective study from a tertiary care institute - Kanhaiyalal Agrawal; Bikash Ranjan Meher; Abhinav Baranwal; Navneet Kumar (Perspectives in Clinical Research)
Introduction: Radiopharmaceuticals (RPs) are used in the diagnosis and management of various cancer and noncancerous conditions. Like those of conventional drugs, the use of RPs may also be associated with the development of various adverse events (AEs). The information obtained from patients about these AEs may empower medical professionals to identify, evaluate, and manage them more efficiently to ensure the safe use of RPs. Objective: The objective of our study was to assess the type, timing, and frequency of the reported AEs associated with the use of RPs and to establish their causal association as well as to evaluate the outcome of these AEs from the perspective of patients. Methods: This study was a prospective cohort study conducted on 315 patients who underwent nuclear medicine examination in a tertiary care center for various indications. Relevant data were collected from the participants regarding suspected AEs associated with the use of various RPs. The collected data were objectively analyzed and assessed. Results: Of 315 patients, 39 (12.3%) developed 59 AEs. All the reported AEs were mild in nature and neither required hospitalization nor caused death of any participants. 37.2% of the reported AEs occurred within 1 h of administration of the RPs and spontaneously resolved within a few hours. Of these 59 AEs, 10 had causal associations (possible or probable) with RPs and were considered adverse drug reaction (ADR). The incidence of ADR in our study was 2.2%. Conclusion: RPs can cause ADRs though it is less in comparison to conventional drugs. We expect that our study will increase the awareness of AEs associated with the use of RPs among patients and health-care professionals and encourage its reporting.